Ether of the Maxwell’s Wave Equation is the Unified Field for Physics - Chandrasekhar Roychoudhuri (Fundamental Research and Application of Physical Science Vol. 3, 2023)
The key purpose of this chapter is to provide extensive examples and rationale to overcome the currently prevailing resistance to accept the physical reality of Cosmic Ether. We identify this integrative power of Ether, first, by re-defining nature’s action generating parameters of this energetic tension field as the electric-tension, electric-tension, \(ε_0^-1\), and the magnetic-resistance, \(μ_0\), while re-deriving the Maxwell’s wave equation in analogy with the mechanically stretched string, where \(c_0^2=ε_0^-1 / μ_0\) is the perpetually moving velocity of light in the free space. Then, the replacement of \(c_0^2\) by \((ε_0^-1 / μ_0)\) and the rest mass \(m_0\) by using Einstein’s \(m_0=E / c_0^2 E(μ_0 / ε_0^-1)\), one can find that almost all working physics theories are being energized by \(ε_0^-1\) and \(μ_0\). To complete the unification, we must assume that the elementary particles are also perpetually moving electromagnetic waves (EM waves) of the same Ether. However, they remain spatially localised and stationary as close-looped, in-phase (CLIP) EM wave modes, obeying the laws of Newton. Only the presence of spatial potential gradients (forces) of the surrounding Ether can move them out of their inertia. CLIP particles’ harmonic phase driven interactions between quantum particles strengthens the successes of the Schrödinger’s equation. The distracting postulates of “plane waves”, and the “Pilot Waves” becomes unnecessary to assist their movements. The cosmic universality of Maxwellian wave velocity, and particles as CLIP modes, jointly accommodate the two key postulates of special relativity without the need for unphysical four-dimensionality. The observable universe is manifest only as diverse oscillatory excited states of the Ether. The stable and stationary Cosmic Ether holds 100% of the cosmic energy all the time.